Floatable, macroporous structured alginate sphere supporting iron nanoparticles used for emergent Cr(VI) spill treatment. (1st August 2016) - Huang, Jian-Fei; Li, Yong-Tao; Wu, Jin-Hua; Cao, Piao-Yang; Liu, Yong-Lin; Jiang, Gang-Biao
Highlights: The alginate-nZVI sphere is great for large-scaled emergent Cr(VI) spill treatment. The alginate-nZVI sphere is effective for Cr(VI) removal in a wide range of pH. The separation of the alginate-nZVI sphere is easy and rapid. After reaction, the generated Cr 3+ can attach on the surface and the sphere inside. The alginate-nZVI sphere is easy processing in large scale production. Abstract: Treatment of hexavalent chromium (Cr(VI)) spill accident is a great challenge due to its high toxicity, sudden and extensiveness. In this study, we designed and fabricated a hierarchical, ordered and macroporous structured alginate sphere to support in-situ synthesized zero-valent iron nanoparticle (the alginate-nZVI sphere). Field emission scanning electron microscope (FESEM) and energy-dispersive X-ray spectroscopy (EDS) images showed well dispersion of nZVI on the composite. This alginate-nZVI sphere exhibited good separability in effective removal of Cr(VI). The result from Cr(VI) removal experiment demonstrated a Cr(VI) removal efficiency of 98.2% at equilibrium time, which can be ascribed to the well dispersion of the nZVI. In addition, the alginate-nZVI sphere was effective in Cr(VI) removal in a wide range of pH from 3.0 to 11.0, by the merit of alginate substrate. Hence, the alginate-nZVI sphere might be a promising agent for an emergent Cr(VI) spill treatment by enhancing the dispersion, stabilization and separation properties of nZVI.